L’algoculture et ses contraintes géographiques en Chine - Sophie Litzler (EchoGéo)
The global aquaculture production has an average annual growth rate of 6.2 per cent (2003-2008). The production of marine plants follows this trend with 15.8 million tons of seaweed farmed. China is the first world farming country with 10 million, tons but in 2008 it reported a 13 per cent drop in its production. Based on this observation, this article intends to show the geographical restrictions that may limit the development of seaweed farming. We shall present an overview of this activity on a global scale then we shall expose a typology of these restrictions. Finally we shall illustrate this research with several case studies.